The effect of sprinting after each set of heavy resistance training on the running speed and jumping performance of young basketball players - Tsimahidis, K.; Galazoulas, C.; Skoufas, D.; Papaiakovou, G.; Bassa, E.; Patikas, D.; Kotzamanidis, C. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to investigate the effect of a 10-week heavy resistance combined with a running training program on the strength, running speed (RS), and vertical jump performance of young basketball players. Twenty-six junior basketball players were equally divided in 2 groups. The control (CON) group performed only technical preparation and the group that followed the combined training program (CTP) performed additionally 5 sets of 8-5 repetition maximum (RM) half squat with 1 30-m sprint after each set. The evaluation took place before training and after the 5th and 10th weeks of training. Apart from the 1RM half squat test, the 10- and 30-m running time was measured using photocells and the jump height (squat, countermovement jump, and drop jump) was estimated taking into account the flight time. The 1RM increased by 30.3 ± 1.5% at the 10th week of training for the CTP group (p < 0.05), whereas the CON group showed no significant increase (1.1 ± 1.6%, p > 0.05). In general, all measured parameters showed a statistically significant increase after the 5th and 10th weeks (p < 0.05), in contrast to the CON group (p > 0.05). This suggests that the applied CTP is beneficial for the strength, RS, and jump height of young basketball players. The observed adaptations in the CTP group could be attributed to learning factors and to a more optimal transfer of the strength gain to running and jumping performance.